Non-linear exchange rate pass-through to euro area inflation: A local projection approach - Roberta Colavecchio; Ieva Rubene (European Central Bank (ECB), 2020)
How long does it take for exchange rate changes to pass through into in ation? Does it make a difference whether the exchange rate depreciates or appreciates? Do relatively large exchange rate changes entail more exchange rate pass-through? In this paper, we examine possible non-linearities in the transmission of exchange rate movements to import and consumer prices in all 19 euro area countries as well as the euro area as a whole from 1997 to 2019Q1. We extend a standard single-equation linear framework with additional interaction terms to account for possible non-linearities and apply local projections to obtain state-dependent impulse response functions. We find that (i) euro area consumer and import prices respond significantly to exchange rate movements after one year, responding more when the exchange rate change is relatively large; and (ii) euro appreciations and depreciations affect the level of euro area exchange rate pass-through in a symmetric fashion; (iii) for euro area countries results differ for import and consumer prices and across countries.
Keywords: E31; F41; 330; Exchange Rate Pass-Through; Ination; Local Projections; Non-Linearities